Bellman filtering for state-space models - Rutger Jan Lange (Tinbergen Institute, 2021)
This article presents a filter for state-space models based on Bellman's dynamic programming principle applied to the mode estimator. The proposed Bellman filter (BF) generalises the Kalman filter (KF) including its extended and iterated versions, while remaining equally inexpensive computationally. The BF is also (unlike the KF) robust under heavy-tailed observation noise and applicable to a wider range of (nonlinear and non-Gaussian) models, involving e.g. count, intensity, duration, volatility and dependence. (Hyper)parameters are estimated by numerically maximising a BF-implied log-likelihood decomposition, which is an alternative to the classic prediction-error decomposition for linear Gaussian models. Simulation studies reveal that the BF performs on par with (or even outperforms) state-of-the-art importance-sampling techniques, while requiring a fraction of the computational cost, being straightforward to implement and offering full scalability to higher dimensional state spaces.
Keywords: C32; C53; C61; 330; dynamic programming; curse of dimensionality; importance sampling; Laplace method; Kalman filter; maximum a posteriori (MAP) estimate; NAIS; particle filter; prediction-error decomposition; posterior mode; Viterbi algorithm